Praktik Mudhārabah Di BMT An-Nawawi Berjan Purworejo Perspektif Hukum Ekonomi Syariah - Nursobah, Achmad (MADINAH, 2020)
BMT An-Nawawi Purworejo is one of the financial institutions that have financing products among them the easy and easy people as a way to advance the economy. As for the mudhārabah products it is the product that partners will be particularly interested in carrying out covenants. But on the ground there have been many cases that for partners feel burdened to return the loan agreed upon in the first place. From that background on the matter to be discussed in this thesis is: what is the review of Islamic law on the mudhārabah practice of BMT An-Nawawi Purworejo? This type of research is field research. As for the data-collecting authors using interviews. Whereas the data analysis technique USES a descriptive method of analysis, which is a procedure or how to solve the research problem by presenting the actual circumstances of the objects (someone, society, etc) as they are based on actual facts at the present time. Once the data has collected, the author will analyze it. The approach can be described in terms of the mudhārabah practice practiced on BMT An-Nawawi Purworejo. The results of this study can be concluded that the mudhārabahpractice performed at BMT An-Nawawi Purworejo is not compatible with Islamic law, because the appropriation for results is determined at the beginning of the agreement.while the result reflect bank interest that is more inclined to usury